Modification of eucalyptus pulp fiber using silane coupling agents with aliphatic side chains of different length. Issue 6 (28th March 2015) - Mendes, Rafael Farinassi; Mendes, Lourival Marin; de Oliveira, Juliano Elvis; Savastano Junior, Holmer; Glenn, Gregory; Tonoli, Gustavo Henrique Denzin
<x xml:space="preserve">Abstract</x> The objective of this work was to evaluate the effect of three silane coupling agents with different aliphatic chain lengths on the hydrophobicity of eucalyptus pulp fiber. The three silanes coupling agents used (isobutyltrimethoxysilane, methyltrimethoxysilane, and n‐octyltriethoxysilane [OTES]) were each tested at three concentrations. Scanning electron microscopy coupled with energy dispersive spectroscopy revealed that the silane coupling agents markedly increased the Si content of the treated fibers. The Si distribution was not completely homogenous but was abundant in the treated samples. The treated fibers had higher contact angles for water and lower moisture adsorption than the control. Of the coupling agents tested, OTES treated fibers had the highest moisture resistance. This was likely due to the greater chain length of the aliphatic side group coupled to OTES. The use of silane coupling agents with alkyl side chains could improve the functional properties of pulp fiber and increase its compatibility with hydrophobic polymers. POLYM. ENG. SCI., 55:1273ȓ1280, 2015. © 2015 Society of Plastics Engineers